Index of financial development with foreign direct investment: Case of Vietnam - Chinh Thi Nguyen; Nguyen Chi Dieu Thi; Van Do Bui (Contemporary Economics, 2023)
This study investigates the effect of the financial development index (FD) on foreign direct investment inflows (FDI) in Vietnam from 1996 to 2021. Time series data are used in the model to assess the influence of six indicators standing for FD. Financial institution assessment (FA), financial depth of institution (FDE), financial efficiency of the institution (FE), financial assessment of market (FM), financial efficiency of the market (FEM), domestic loans for the private sector (DLP) was collected from 1996 to 2021. As a result of the analysis, when FA, FE, and FEM increase, Vietnam's FDI inflow also increases while FDE and FM decrease FDI. The effect of DLP is unclear, and this study has no significant association. It is found that the selected financial development index has a significant impact on attracting inward FDI. It is also necessary for the government and officials to make appropriate policies in the future.
Keywords: F15; F21; G10; G23; 330; financial development; financial development index; foreign direct investment; Vietnam